Tariffication Strategy in Telecommunication Business - Gustav Cepciansky (Advances in Electrical and Electronic Engineering, 2004)
The tariff policy of a telecommunication operator has a strategic importance on achieving of optimal revenues and a fundamental impact on its position in the competition with another operators on the liberalised telecommunication market. The payment for a connection through a telecommunication network is determined by a rate for one call unit, by the duration of the call unit and their count during a call. An operator derives the rate and the duration of the call unit from a detailed analysis of large databases that contain statistical data on counts and duration of particular calls depending on the call type. Only the operator knows these data files and it keeps them confidential. It will be shown in the paper how it is possible to come to an estimation of revenues from telecommunication traffic only knowing a pair of basic parameters. The first considerations handling with this topic can be found in [1], [2],[3].